2012
DOI: 10.1128/cvi.00313-12
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Assay Detection of Immunoglobulin G Antibodies That Recognize Babesia microti Antigens

Abstract: Human babesiosis, a blood-borne infection caused by several species of Babesia, including B. microti, is an emerging disease that is endemic in the Northeast, upper Midwest, and Pacific Northwest regions of the United States. Risk factors for babesiosis include exposure to the infected tick vector and blood transfusions from infected donors. In this work, we cloned and expressed two of the immunodominant antigens from B. microti and used them in a multiplex bead format assay (MBA) to detect parasitespecific Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…S5, available as supporting information in the online version of this paper). BmSA1 was used in a multiplex assay to detect B. microti IgG antibodies and showed specificity and sensitivity levels similar to those reported in this study for BmGPI12 . Our studies revealed that B. microti expresses a smaller set of GPI‐anchored proteins than that of P. falciparum .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…S5, available as supporting information in the online version of this paper). BmSA1 was used in a multiplex assay to detect B. microti IgG antibodies and showed specificity and sensitivity levels similar to those reported in this study for BmGPI12 . Our studies revealed that B. microti expresses a smaller set of GPI‐anchored proteins than that of P. falciparum .…”
Section: Discussionsupporting
confidence: 79%
“…BmSA1 was used in a multiplex assay to detect B. microti IgG antibodies and showed specificity and sensitivity levels similar to those reported in this study for BmGPI12. 10,38,41,61 Our studies revealed that B. microti expresses a smaller set of GPI-anchored proteins than that of P. falciparum. 21 The predicted GPI-anchored proteins of B. microti expressed in the blood stage of the parasite are different from those of P. falciparum and Toxoplasma gondii parasites.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…20 In brief, the EIA uses four peptide antigens derived from two members of the BMN1 gene family, BMN1-9 (also termed BmSA1) and BMN1-17, which have been shown to be immunodominant in prior studies. 21-23 The four peptide antigens were identified by screening candidate peptides against a library of sera from patients with clinically diagnosed babesiosis as well as healthy controls. The biotinylated peptides were immobilized on streptavidin-coated microplates (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…IgG4 plays a role in both diseases, although that role is yet undefined. The monoclonal anti-IgG4 (clone HP6025; Zymed) antibodies verified to test for Babesiosis, imply that IgG4 is indeed present and in Babesiosis [19]. IgG4 levels have also been used to track responsiveness of RPF IgG4 related disease during treatment courses of rituximab and have been found to be a prognosticating factor [13].…”
Section: Discussionmentioning
confidence: 99%